Body drop notes on fandom and pain in professional wrestling - Oliu, Brian (The University of North Carolina Press, 2021)
"Professional wrestling is a strange beast full of contradictions--it's part live soap opera, part hyper-masculine violent spectacle. It is an indelibly American pastime enjoyed by millions and leads a select group of wrestlers to international fame. It's also a sport that leaves many of its athletes broken and battered, at serious risk of addiction, poverty, and early death. Body drop looks deeply at the nuances of professional wrestling and its strange place within American culture. Brian Oliu offers deeply personal meditations on such topics as disability, chronic pain, body image, masculinity, class, and more, all through the lens of American professional wrestling"--